2014
DOI: 10.1002/2014ja020599
|View full text |Cite
|
Sign up to set email alerts
|

A new method to estimate annual solar wind parameters and contributions of different solar wind structures to geomagnetic activity

Abstract: In this paper, we study two sets of local geomagnetic indices from 26 stations using the principal component and the independent component (IC) analysis methods. We demonstrate that the annually averaged indices can be accurately represented as linear combinations of two first components with weights systematically depending on latitude. We show that the annual contributions of coronal mass ejections (CMEs) and high‐speed streams (HSSs) to geomagnetic activity are highly correlated with the first and second IC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
0
20
0
7
Order By: Relevance
“…Previous studies have shown that solar wind speed is an important driver of long‐term (e.g., monthly and yearly) geomagnetic activity at low latitudes and midlatitude (Akasofu, ; Crooker, Feynman, & Gosling, ; Richardson, Cane, & Cliver, ; Richardson, Cliver, & Cane, ) and, especially, at high latitudes (Finch et al, ; Holappa, Mursula, & Asikainen, ; Holappa, Mursula, Asikainen, & Richardson, ; Lukianova, Mursula, & Kozlovsky, ; Mursula, Holappa, & Lukianova, ; Mursula, Lukianova, & Holappa, ) and of substorm activity (Tanskanen et al, ). Here we study to what extent the solar wind speed controls the seasonal variation of high‐latitude geomagnetic activity.…”
Section: Seasonal Variation Of Solar Wind Speed In 1995–2014mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that solar wind speed is an important driver of long‐term (e.g., monthly and yearly) geomagnetic activity at low latitudes and midlatitude (Akasofu, ; Crooker, Feynman, & Gosling, ; Richardson, Cane, & Cliver, ; Richardson, Cliver, & Cane, ) and, especially, at high latitudes (Finch et al, ; Holappa, Mursula, & Asikainen, ; Holappa, Mursula, Asikainen, & Richardson, ; Lukianova, Mursula, & Kozlovsky, ; Mursula, Holappa, & Lukianova, ; Mursula, Lukianova, & Holappa, ) and of substorm activity (Tanskanen et al, ). Here we study to what extent the solar wind speed controls the seasonal variation of high‐latitude geomagnetic activity.…”
Section: Seasonal Variation Of Solar Wind Speed In 1995–2014mentioning
confidence: 99%
“…We would also like to note that even though the long‐term averages (e.g., monthly means) of high‐latitude indices, like the IL index, are mainly driven by high‐speed streams, they are also somewhat affected by transients like coronal mass ejections (see, e.g., Holappa, Mursula, & Asikainen, , Holappa, Mursula, Asikainen, & Richardson, ). However, the seasonal variation of high‐latitude indices based on the monthly values is predominantly determined by high‐speed streams.…”
Section: Seasonal Variation Of Solar Wind Speed In 1995–2014mentioning
confidence: 99%
“…The main solar wind drivers of geomagnetic activity are interplanetary coronal mass ejections (ICME) and high‐speed streams (HSS) together with corotating interaction regions (CIR) (Richardson & Cane, ; Sawyer & Haurwitz, ; Tanskanen et al, ; Zhang et al, ). However, the relationship of HSSs and ICMEs to geomagnetic activity at different latitudes, as well as their occurrence over the solar cycle, varies considerably (Holappa et al, ; Holappa, Mursula, & Asikainen, ).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the average geomagnetic activity during the passage of CMEs is stronger than during the passage of HSSs. Holappa et al [] recently developed a method to extract CME and HSS contributions to geomagnetic activity using independent component analysis. They confirmed that the CME‐ and HSS‐related geomagnetic activity peak in the solar maxima and declining phase, respectively, and also found that the amplitude of these two components over several solar cycles is similar.…”
Section: Introductionmentioning
confidence: 99%